The dopamine, serotonin and norepinephrine releasing activities of a series of methcathinone analogs in male rat brain synaptosomes - Blough, Bruce E. (Psychopharmacology (Berl), 2018)
RATIONALE. Novel synthetic ‘bath salt’ cathinones continue to appear on the street as abused and addictive drugs. The range of subjective experiences produced by different cathinones suggests that some compounds have primarily dopaminergic activity (possible stimulants) while others have primarily serotonergic activity (possible empathogenics). An understanding of the structure activity relationships (SARs) of these compounds will help in assessing the likely behavioral effects of future novel structures, and to define potential therapeutic strategies to reverse any reinforcing effects. OBJECTIVES. A series of methcathinone analogues was systematically studied for their activity at the dopamine and serotonin transporters. Compound structures varied at the aromatic group, either by substituent or by replacement of the phenyl ring with a naphthalene or indole ring. METHODS. A novel, high yielding synthesis of methcathinone hydrochlorides was developed which avoids isolation of the unstable free bases. Neurotransmitter transporter release activity was determined in rat brain synaptosomes as previously reported. Compounds were also screened for activity at the norepinephrine transporter. RESULTS. Twenty-eight methcathinone analogs were analyzed and fully characterized in dopamine and serotonin transporter release assays. Compounds substituted at the 2-position (ortho) were primarily dopaminergic. Compounds substituted at the 3-position (meta) were found to be much less dopaminergic, with some substituents favoring serotonergic activity. Compounds substituted at the 4position (para) were found to be far more serotonergic, as were disubstituted compounds and other large aromatic groups. One exception was the fluoro substituted analogs which seem to favor the dopamine transporter. CONCLUSIONS. The dopaminergic to serotonergic ratio can be manipulated by choice of substituent and location on the aromatic ring. It is therefore likely possible to tweak the subjective and reinforcing effects of these compounds by adjusting their structure. Certain substituents like a fluoro group tend to favor the dopamine transporter, while others like a trifluoromethyl group favor the serotonin transporter.